FINANCIAL STATEMENT FRAUD IN PT WIJAYA KARYA (PERSERO) TBK FOR THE PERIOD 2019-2023 - Nur Hayati; M Adhitya Wardhana; Herri Wijaya (JURNAL BISNIS DIGITAL DAN SISTEM INFORMASI, 2024)
This study examines the financial performance of PT Wijaya Karya Tbk, whose stock trading has been suspended since December 18, 2023 by the Indonesia Stock Exchange. This research uses a literature study method which uses data in the form of PT Wijaya Karya Tbk's financial statements from 2019 to 2023. The results of the analysis conducted show that there is a worsening financial condition characterized by decreasing total assets, decreasing cash reserves, and increasing short-term debt. The company's inability to meet its debt obligations can be seen from the worsening debt to equity ratio and negative operating cash flow. Further analysis of the financial ratios, especially those related to receivables, inventories, and revenues, indicated potential financial statement fraud. The study concluded that a combination of factors, including poor financial management and potential fraudulent activities, contributed to the company's financial crisis. To prevent such occurrences in the future, improved corporate governance, tighter internal controls, and increased transparency are essential.